2016
DOI: 10.17576/pengurusan-2016-46-11
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility for Takaful Industry’s Branding Image

Abstract: This study attempts to confirm the likelihood of Corporate Social Responsibility (CSR) activities giving different effects on brand image components and whether corporate reputation mediates these effects. Four action-based types of CSR, namely the economic, legal, ethical and philanthropic, were analyzed and tested in this study. This study employs quantitative method of analysis whereby the participants were exposed to different treatments and the brand image was divided into an affective, specific and gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…This argument is consistent with the view of other scholars who described mixed evidence in the relationship, but most studies were found to show positive relationship [62]. While some studies found CSR as an increaser of business performance [26,41,42], other scholars documented negative [63] or no relationship [54] between the CSR practices of an organization and its performance. Even though scholars found mixed results of correlation between social responsibility and financial performance, society still desires a firm to implement good social responsibility and environmental management practices [64].…”
Section: Environment As Moderatorsupporting
confidence: 88%
See 3 more Smart Citations
“…This argument is consistent with the view of other scholars who described mixed evidence in the relationship, but most studies were found to show positive relationship [62]. While some studies found CSR as an increaser of business performance [26,41,42], other scholars documented negative [63] or no relationship [54] between the CSR practices of an organization and its performance. Even though scholars found mixed results of correlation between social responsibility and financial performance, society still desires a firm to implement good social responsibility and environmental management practices [64].…”
Section: Environment As Moderatorsupporting
confidence: 88%
“…The classical view of the concept postulated that CSR entails activities meant to generate and increase profit only [37]; while the instrumental theory asserts that organizations should support social activities to gain a good image and competitive advantage [38]. Indeed, a corporation should fulfill the expectations of society and different stakeholders [26] to survive in business [39,40].…”
Section: Corporate Social Responsibility (Csr) and Firm Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Hence, based on the number of important aspects of the rationale for conducting several CSR activities, the survey divided the cognitive image into an effective image, generic cognitive image and a specific cognitive image component that fits all the relevant standards. This approach conforms to the idea that associations of those affected can be divided into micro-associations that specifically address the level and number of interest groups and metaassociations, whereby all parties are of equal importance to all stakeholders [13]. Moreover, various types of brand image components build the brand image.…”
Section: Brand Imagementioning
confidence: 99%